Radioiodine-resistant metastases of well-differentiated thyroid cancer, analysis of tumor characteristics and primary surgical intervention - Ostafiychuk, M. V.; Kovalenko, A. Ye.; Tarashchenko, Yu. M. (Zaporozhye Medical Journal, 2021)
The aim of this article is to assess the initial status, characteristics of the tumor process and initial surgical treatment in patients with well-differentiated thyroid carcinomas who subsequently showed resistance to 131I therapy, comparing with the control group of patients who achieved a positive effect of 131I therapy. Materials and methods. In total, 156 cases of well-differentiated thyroid cancer were analyzed. The control group consisted of 189 patients who showed complete responses to treatment of metastases after 131I therapy and the confirmed relapse-free period. The patients were operated and followed up in the Department of Endocrine Gland Surgery of SI “V. P. Komisarenko Institute of Endocrinology and Metabolism of the National Academy of Medical Sciences of Ukraine” between 1990 and 2019. Results. Based on our study, in the group of radioiodine-resistant metastases, there was a 3.1:1.0 predominance of women over men; whereas in the control group, this ratio was 1.4:1.0. It was noted that resistance to radioactive iodine in patients under 20 years of age was 4 times significantly lower (10.26 %) comparing with the radiosensitive group (41.90 %). In the age group of 41–60 years, radioiodine resistance was 6.5 times higher than that in the comparison group (39.10 % and 6.35 %), and in the age group over 61 years – 11 times (11.54 % and 1.05 %). The impact analysis of radiation exposure on the radioiodine refractoriness occurrence revealed that among patients living in radiation-contaminated areas of Ukraine in 1986 following the Chornobyl accident, there were no significant differences in the development of resistance to radioactive iodine (resistance to 131I – 51.92 % (n = 81), treatment response 131I – 64.02 % (n = 121)). These differences may be due to the younger age of patients affected by radiation and better sensitivity to radioiodine compared to the main group patients. The maximum number of radioiodine-resistant observations was in the intermediate risk group (71.15 %; n = 111). Worth noting is the significant number of radioiodine-resistant metastases in the group where their absence was initially diagnosed (11.53 %; n = 18) and in the group where the proper assessment of lymph collectors was not performed (29.49 %; n = 46). Radioiodine resistance was significantly more common (33.97 %; n = 53) in observations where the prophylactic central dissection was not performed. Conclusions. The main risk factors in the development of radioiodine-resistant metastases were the age of patients older than 40 years, the limited primary surgery on regional lymphatic collectors of the neck, tumor aggressiveness. Careful pre- and intraoperative assessment of regional collectors of the lymph outflow, preventive central neck dissection and extensive therapeutic dissections can reduce the risk of residual and radioiodine-resistant metastases. Timely diagnosis of metastases can improve the results of primary surgical treatment for patients with differentiated thyroid carcinoma and reduce the incidence of radioiodine resistance.